Severe cerebral vasospasm following non-K1 meningitis: a case report - Cameron Stewart; Tao Hong; Anuoluwapo A. Shobayo; Jessica E. Chang; Thanujaa Subramaniam (Journal of Neurocritical Care)
Background Cerebral vasospasm has been reported following various forms of bacterial meningitis; however, there have been no prior reports of meningitis caused by the non-K1 strain of Escherichia coli. Case Report A 63-year-old man with chronic thrombocytopenia presented with new-onset seizures that progressed to coma. Cerebrospinal fluid (CSF) analysis showed Gram-negative rods, but CSF culture and the Biofire FilmArray Meningitis/Encephalitis Panel were negative. Additional 16S ribosomal ribonucleic acid (rRNA) polymerase chain reaction and sequencing of the CSF sample indicated E. coli meningitis when correlated with the results of urine culture. The patient eventually developed diffuse cerebral arterial vasospasms with multifocal brain infarcts that progressed to brain death. Conclusion E. coli meningitis in adults may be missed if diagnostic tests include only K1 strains. Clinicians should be aware of cerebral vasospasm as a potentially serious complication of E. coli meningitis, and should consider screening for it, particularly in patients with associated risk factors.